Densification of amorphous calcium phosphate using principles of the cold sintering process. Issue 1 (January 2021) - Rubenis, Kristaps; Zemjane, Signe; Vecstaudza, Jana; Bitenieks, Juris; Locs, Janis
Abstract: Despite considerable interest in amorphous calcium phosphate (ACP) bioceramics, it remains a challenge to sinter ACP to high relative density. Here, for sintering of ACP, we used principles of the so-called cold sintering process. We investigated the effect of sintering temperature (room temperature, 100, 120 and 150 °C) and presence or absence of transient liquid (20 wt. % water), while holding the pressure applied at 500 MPa, on densification and structure of ACP. Relative density of the samples that were produced from the dry starting powder at room temperature (the samples retained ACP structure) already reached 76.3 (±2.1) %. Neither increased sintering temperature nor the presence of transient liquid significantly affected bulk, true and the resulting relative density values of the samples that retained ACP structure. Our findings indicate that by applying moderate uniaxial pressure, ACP can be sintered to relatively high relative density already at room temperature.